Functional state of the small airways in patients with bronchial asthma associated with obesity - E E Mineeva (Терапевтический архив, 2019)
Aim. To assess the functional status of the small Airways in patients with bronchial asthma associated with obesity, by body plethysmography. Materials and methods. 65 patients with bronchial asthma of mild severity, partially controlled course, including 30 patients with normal body weight and 35 patients with obesity of I degree were examined. Control group-30 healthy volunteers. Examined forced vital capacity (FVC), forced expiratory volume in first second (FEV1) ratio of FEV1 to FVC (FEV1/FVC), maximum volumetric exhalation rate after 25.50 and 75% FVC (MEF75, MEF50, MEF25), average flow velocity in the exhalation interval 25-75% of FVC (MMEF25-75). Method bodyplethysmography was evaluated in bronchial resistance, functional residual capacity (FRC), residual volume of the lungs (RV), total lung capacity (TLC), the percentage of RV/TLC. Results. Patients with bronchial asthma with obesity showed a reduction of indicators of bronchial obstruction: FEV1 of 14% (p=0.02), FEV1/FVC by 14% (p=0.001), MEF75 30% (p=0.001), MEF50 by 35% (p=0.001), MEF25 by 44% (p=0.003), MMEF25-75 by 38% (p=0.001). The increase of bronchial resistance on inhalation in 2 times (p=0.001), on exhalation in 3.3 times (p=0.003) was found, which is typical for generalized bronchial obstruction at the proximal level. An increase in RV by 24% (p=0.03), TLC - by 9% (p=0.03), RV/TLC - by 18% (p=0.03), indicating the presence of "air traps" and dysfunction of the small respiratory tract. Conclusion. In patients with asthma of mild severity associated with obesity, both the central bronchis and the distal lung are affected, which are manifested by generalized bronchial obstruction, the formation of "air traps" and dysfunction of the small respiratory tract.